2019
DOI: 10.20502/rbg.v20i1.1264
|View full text |Cite
|
Sign up to set email alerts
|

O Papel Da Dinâmica Do Relevo Na Evolução De Couraças No Vale Do Rio Conceição, Quadrilátero Ferrífero – Mg

Abstract: Estudos petrológicos utilizando análises macromorfológicas, micromorfológicas, mineralógicas e microquímicas foram realizados para identificar possíveis variações faciológicas de couraças nos distintos níveis deposicionais fluviais do vale da bacia do Rio Conceição, Quadrilátero Ferrífero, Minas Gerais, e compreender sua relação com o relevo. Sua posição na paisagem sugere que estas sejam as couraças mais jovens do Quadrilátero Ferrífero e que sua formação testemunhe a dinâmica de formação e transformação dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, from the analysis of other samples of the same aluminous conglomeratic type investigated in this study, Figueiredo Filho et al (2019) considered that the micromorphological organisations observed and the relationship between them suggest a stronger origin related to the degradation processes of pre‐existing ferruginous ferricretes. Gibbsite is present in two ways in the ferricretes analysed by these authors: (i) complete formation of the cement that separates the clasts (facies F1) and (ii) discontinuous and always at the edge of the septa and microlaminated zones, whose microchemical analysis revealed an iron‐aluminous composition (F2 facies).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, from the analysis of other samples of the same aluminous conglomeratic type investigated in this study, Figueiredo Filho et al (2019) considered that the micromorphological organisations observed and the relationship between them suggest a stronger origin related to the degradation processes of pre‐existing ferruginous ferricretes. Gibbsite is present in two ways in the ferricretes analysed by these authors: (i) complete formation of the cement that separates the clasts (facies F1) and (ii) discontinuous and always at the edge of the septa and microlaminated zones, whose microchemical analysis revealed an iron‐aluminous composition (F2 facies).…”
Section: Discussionmentioning
confidence: 76%
“…Studies developed to date on this type of duricrust have focused on their regional topographic distribution and have revealed Pleistocene to Holocene ages (~139–83, ~47 and ~26 ka) for sediments associated with the duricrusts (Barros & Magalhães, 2019, 2020). The only petrogenetic study developed to elucidate the genesis of duricrusts in fluvial archives was restricted to the Conceição River valley (Figueiredo Filho et al, 2019). In turn, this study aimed to analyse duricrusts in the Late Pleistocene fluvial archives of the entire QF, searching for their genesis and implications for regional landscape evolution.…”
Section: Introductionmentioning
confidence: 99%